STUDI EVALUASI PENGELOLAAN PROGRAM BIMBINGAN DAN KONSELING DI SMAN I KOTA BENGKULU DAN SMAN 11 KOTA BENGKULU - agus hermawan; I Wayan Dharmayana (UNIVERSITAS BENGKULU, 2020)
Abstract: This research is a descriptive evaluation research. The approach used is a systems approach that is focused on planning, implementing, and evaluating counseling programs in Bengkulu City High School. The subjects of this study were the management of counseling guidance programs at SMAN 1 Bengkulu City and SMAN 11 Bengkulu City. Data collection was carried out through interviews, observations, research questionnaire instruments and documentation. The results of the research on the management of the guidance and counseling program based on the Minister of Education and Culture Regulation No. 111 of 2014 concerning Guidance and Counseling in Basic Education and Secondary Education at SMAN 1 Bengkulu City have very good criteria with a percentage of 77% (excellent) implemented. Whereas SMAN 11 Bengkulu City has good criteria with a percentage of 63% (good) implemented.